2002
DOI: 10.1007/s00264-002-0342-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of displaced fractures of the glenoid cavity

Abstract: Between 1994 and 1999 ten patients with displaced glenoid cavity fractures were treated operatively. Nine of the fractures were the result of road traffic accidents. There were eight men and two women patients, their average age was 38 (range 22-54) years, and the follow-up ranged from 18 to 84 months. Functional outcome was assessed in terms of pain, range of movement, muscle power, and performance of daily activities, and the results were excellent or good in eight patients.Résumé Entre 1994 à 1999 nous avon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 5 publications
0
49
0
Order By: Relevance
“…They noted that fair and poor outcomes were related to concomitant injuries. Adam [6] reported eight out of ten good to excellent results in another series on glenoid fractures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They noted that fair and poor outcomes were related to concomitant injuries. Adam [6] reported eight out of ten good to excellent results in another series on glenoid fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are a limited number of studies [6][7][8][9][10][11][12][13][14], mostly case series with a relatively small number of patients, there has been increasing evidence that certain scapular fractures require operative treatment to optimize functional results. The purpose of this study was to review the functional outcomes of scapular fractures treated surgically at a level one trauma center.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsurgical management avoids general surgical risks (painful hardware [22], infection, brachial plexus palsy [2], hematoma [17,29]) and risks associated with the posterior Judet approach especially when excessive dissection for exposure of the infraspinatus fossa is required (risk of iatrogenic damage of the infraspinatus branch of the suprascapular nerve and scar formation along soft tissue planes [12,18]). Other authors have reported good outcomes with nonoperative management of scapular body fractures [4,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Ten to forty percent of these involves scapular neck, and out of these, only 10% are displaced and indicative of operative intervention (1, 4-7). The most common mechanism of injury for scapular fractures is a direct and high energy violent impact, which frequently affects the body of the scapula.…”
Section: Introductionmentioning
confidence: 99%